2001
DOI: 10.1097/00000658-200108000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Hepatocellular Carcinoma Without Preoperative Tumor Biopsy

Abstract: ObjectiveTo evaluate the need for a preoperative tumor biopsy of liver lesions suspicious for hepatocellular carcinoma (HCC). Summary Background DataWith advances in liver imaging, the results of recent studies have suggested a very high accuracy of preoperative evaluation of liver masses suspicious of HCC, making preoperative tumor biopsy unnecessary. MethodsA retrospective analysis was conducted of all liver resections for HCC at the Toronto General and Mt. Sinai Hospitals, Toronto, between October 1994 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 17 publications
1
56
1
6
Order By: Relevance
“…If AFP is greater than 200 ng/mL and the radiological appearance of the mass is suggestive of HCC (large and/or mutifocal disease with arterial hypervascularity), the likelihood that the lesion is HCC is high and biopsy is not essential. 151,152 If the imaging appearances are atypical, the differential diagnosis is broader, and tumor biospy should be considered.…”
Section: Lesions >2 CM In Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…If AFP is greater than 200 ng/mL and the radiological appearance of the mass is suggestive of HCC (large and/or mutifocal disease with arterial hypervascularity), the likelihood that the lesion is HCC is high and biopsy is not essential. 151,152 If the imaging appearances are atypical, the differential diagnosis is broader, and tumor biospy should be considered.…”
Section: Lesions >2 CM In Diametermentioning
confidence: 99%
“…Such lesions should be treated as HCC 3,151,152 since the positive predictive value of the clinical and radiological findings exceeds 95%. 3,151,152 If the vascular profile on dynamic imaging is not characteristic and the AFP is less than 200 ng/mL a biopsy is recommended. More recently the value of "washout" in the venous phase has been recognized.…”
Section: Lesions >2 CM In Diametermentioning
confidence: 99%
“…However false-positive results from imaging techniques have also occurred. 14,15 Now there is a need to decide the strategy accordingly in an individual patient. It has to be weighed whether the risk of futile transplantation is more or the risk of seeding?…”
Section: Is Tissue Diagnosis Required?mentioning
confidence: 99%
“…Otherwise, these lesions should not be treated as HCC without histological evidence because of a rate of false positives as high as 20%. 14,15 Recent prospective studies have reported that up to 67% of new nodules smaller than 2 cm identified during surveillance imaging in patients with cirrhosis are indeed HCC. 16 Although the specificity of contrast enhanced MRI has been reported as high as 96% for hepatic nodules of 1-2 cm in size, a significant proportion of small HCC may appear hypovascular or have atypical features, resulting in a false-negative rate of 20%-38%.…”
mentioning
confidence: 99%
“…A feature of liver cancer is that it allows for diagnosis with non-invasive examination without a liver biopsy [4]. The sensitivity and specificity of non-invasive diagnosis for liver cancer with nodules >2 cm and cirrhosis are more than 95% [5,6]. We report a case that was misdiagnosed as liver cancer using ultrasound, multi-detector computed tomography (MDCT), and Gd-EOB-DTPA-enhanced magnetic resonance imaging (MRI), and confirmed as liver IPT by biopsy.…”
Section: Introductionmentioning
confidence: 99%